RATU PIRAKAS Rak Sepatu Pipa Paralon Bekas (Parallel Pipe Shoe Rack) - Miftahurrohman -; Tin Rosidah; Erlina -; Tsania Filhil Masyhana (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
"RATU PIRAKAS" The Paralon Pipe Shoe Shelf is the latest innovation that utilizes used paralon pipes as thebasic material for making shoe racks. Shoe shelving can reduce waste or be environmentally friendly and canincrease income for students. "RATU PIRAKAS" The Paralon Pipe Shoe Shelf was developed as a brilliantstudent idea, to reduce waste from households that are widely available in Semarang. So with the productcreativity of students in the form of "RATU PIRAKAS" this can recycle paralon pipe waste into goods that areready to use, high selling value and environmentally friendly. The method used to make used parallel pipes is tomake a shoe rack design, collect used paralon pipes, cut paralon pipes, wash and sandpipe paralon pipes, rack updesigns, paint shelves, and pack. So far the resulting product has been good, but no one has been sold due to themarketing process that has not been widespread, especially among the general public. Some problems encountered in the process of making "RATU PIRAKAS" this is the lack of manpower for the work, lack of coordination between members and the timing of unscheduled work. Our hope, student creativity products in the form: "RATU PIRAKAS" Pallet Shoe Shelf Paralon Used, acceptable to the community, and can increase student income. In addition creativity made from paralon pipes used to contribute to save the world from environmental pollution by using household waste that now generates a lot of waste in the form of used paralon pipes.Keywords: Ratu Pirakas, Trash, Pipe Paralon Used